ФЕНОМЕН «ТВОРЧИЙ ПОТЕНЦІАЛ ОСОБИСТОСТІ» У ПСИХОЛОГО-ПЕДАГОГІЧНИХ ДОСЛІДЖЕННЯХ - Канішевська, Любов (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглянуто концептуальні підходи щодо визначення феномена «творчий потенціал особистості» у вітчизняних та зарубіжних психолого-педагогічних дослідженнях. Визначено, що більшість дослідників є прихильниками позиції, що творчий потенціал особистості – складна структура, що включає емоційну культуру, систему культурологічних, професійно-педагогічних знань, широку загальнокультурну ерудицію, генетичне задане обдарування, образне мислення, здатність моделювати різноманітні способи творчої діяльності; здатність особистості до перетворення, до створення нового. В статье рассматриваются концептуальные подходы к определению феномена «творческий потенциал личности» в отечественных и зарубежных психолого-педагогических исследованиях. Определено, что большинство исследователей являются приверженцами позиции, что творческий потенциал личности – сложная структура, которая включает эмоциональную культуру, систему культурологических, профессионально-педагогических знаний, широкую общекультурную эрудицию, генетически данную одаренность, образное мышление, способность моделировать разнообразные способы творческой деятельности; способность личности к преобразованию, к созданию нового. The article discusses the conceptual approaches to the phenomenon of «individual creative potential» definition in native and foreign psychological and pedagogical research. Determined that most researchers are committed to the position that individual creativity – a complex structure that includes emotional culture, system of cultural, professional and pedagogical knowledge, broad general cultural erudition, genetic given talent, creative thinking, the ability to simulate various ways creative activity; the ability of the individual to transform, to create a new one. Analysis of psychological and educational research reveals that the researchers consider the essence of the concept of «individual creativity» as: quality system of personality associated with research activity; the ability of the individual to decide unconventional contradictions arising in real life; integrative personal property, as reflected in the attitude (position instruction, orientation) individual creativity; system characteristics of personality, thanks to which it can work, make decisions, think outside the box and diyalt; a number of factors: the makings (as an innate quality), social environment (external environment influence) and personal activity (individual life position); the ability of the individual, allowing act outside the box, get a new, original results.